Recent advances in the synthesis of xanthones and azaxanthones - Diana I S P Resende; Durães, Fernando; Maia, Miguel; Sousa, Emília; Pinto, Madalena M M (Organic chemistry frontiers an international journal of organic chemistry, 2020)
Xanthones are important O-heteroaromatic tricyclic molecules exhibiting a wide range of bioactivities and can represent a showcase to highlight the recent techniques and strategies in organic synthesis towards lead discovery and optimization. This review gives an insight into the recent literature disclosed to obtain the xanthone core, including the drug-like azaxanthones, isosteres of xanthones, by exploiting the optimization of well-known procedures as well as disruptive developed methodologies. With this review, it is expected to provide a useful chemical toolbox to synthetic medicinal chemistry focusing on these privileged structures, covering from 2012 to 2020, with some older examples of azaxanthones.